A new synonym of Neomida luteonotata (Pic, 1926) (Coleoptera: Tenebrionidae: Diaperini) - Aloquio, Sergio; Flores, Gustavo E.; Lopes-Andrade, Cristiano (Zootaxa, 2017)
The genus Neomida Latreille, 1829 (Tenebrionidae: Diaperini) comprises 42 species in the New World (Triplehorn, 2006). Species from America north of Colombia have been recently revised in detail by Triplehorn (2006), who additionally provided general notes on other New World representatives. One of these taxa was Neomida luteonotata (Pic, 1926). This species is easily recognized among its congeners by the unique elytral coloration, which consists of a large shield-shaped black spot in the middle and yellowish to reddish brown area around it. The area of the elytra covered by the median spot is highly variable within a single population. In some individuals it reaches the elytral sides, confining the light area to the bottom and apex of elytra.